Kompetensi Profesional Guru dalam Mendukung Peserta Didik dengan Kesulitan Belajar Ringan dalam Pendidikan Inklusif: A Systematic Literature Review - Fajrina, Syifa; Takdir, Supadi; Listyasari, Winda Dewi; Kamaludin (Media Manajemen Pendidikan, 2026)
This study aims to map research developments on teachers’ professional competence in inclusive education and to identify competencies relevant to supporting students with mild learning difficulties (slow learners). A Systematic Literature Review (SLR) was conducted following PRISMA guidelines. Literature searches in Scopus and Google Scholar covering the 2021–2025 period yielded 181 initial articles, of which 24 met the inclusion criteria. The methodological quality of the selected studies was appraised using the Mixed Methods Appraisal Tool (MMAT). Data were analyzed through thematic synthesis and bibliometric analysis using VOSviewer to explore conceptual structures and research trends. The findings indicate that existing studies predominantly focus on inclusive education and teacher professional development, while slow learners remain a relatively marginal topic. Six key dimensions of teachers’ professional competence were identified: diagnostic–formative assessment, pedagogical differentiation, technology and assistive integration, social–emotional support, professional collaboration, and engagement within supportive institutional ecosystems. This review offers a concise conceptual framework and practical implications for strengthening teacher professional development in inclusive education context.